2005
DOI: 10.1007/s00228-005-0057-z
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype-genotype analysis of CYP1A2 in Japanese patients receiving oral theophylline therapy

Abstract: These results suggest that the CYP1A2*1C and CYP1A2*1F genotypes are not crucial factors for the variability of CYP1A2 activity and that the CYP1A2*1K haplotype is either nil or only shows a very low frequency in Japanese.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 21 publications
3
18
0
Order By: Relevance
“…We did not find a functional effect of any of the CYP1A2 SNPs, haplotypes, or diplotypes identified, which is consistent with the previous studies [Jiang et al, 2006;Takata et al, 2006]. Other studies, however, have reported otherwise.…”
Section: Discussionsupporting
confidence: 91%
“…We did not find a functional effect of any of the CYP1A2 SNPs, haplotypes, or diplotypes identified, which is consistent with the previous studies [Jiang et al, 2006;Takata et al, 2006]. Other studies, however, have reported otherwise.…”
Section: Discussionsupporting
confidence: 91%
“…Some studies found decreased enzyme activity or inducibility associated with the A allele [18], [44]. Other studies found no difference in the enzyme activities or inducibility between the G and A alleles [21], [45]. One study reported the A allele was related to increased CYP1A2 activity [46].…”
Section: Discussionmentioning
confidence: 99%
“…It is not quite clear yet how much the CYP1A2*1F allele influences actual enzyme activity. When caffeine metabolites were measured, enzyme activity was higher among carriers of the CYP1A2*1F allele in one [33], but not in another report [34]. Given the stronger association of percent density with progesterone than estrogens [3,7], polymorphisms related to progestin metabolism may provide additional insights.…”
Section: Discussionmentioning
confidence: 99%